Characterization of the Grp94/OS-9 chaperone-lectin complex - Seidler, Paul M. (2014)
Grp94 is a macromolecular chaperone belonging to the hsp90 family and is the most abundant glycoprotein in the endoplasmic reticulum of mammals. In addition to its essential role in protein folding, Grp94 was proposed to participate in the ER associated degradation (ERAD) quality control pathway by interacting with the lectin OS-9, a sensor for terminally misfolded proteins (TMPs). To understand how OS-9 interacts with ER chaperone proteins, we mapped its interaction with Grp94. Glycosylation of the full length Grp94 protein was essential for OS-9 binding, although deletion of the Grp94 N-terminal domain relieved this requirement suggesting that the effect was allosteric rather than direct. Although yeast OS-9 is composed of a well-established N-terminal MRH lectin domain and a C-terminal dimerization domain, we find that the C-terminal domain of OS-9 in higher eukaryotes contains ‘mammalian-specific insets’ that are specifically recognized by the middle and C-terminal domains of Grp94. Additionally, the Grp94 binding domain in OS-9 was found to be intrinsically disordered. The biochemical analysis of the interacting regions provides insight into the manner by which the two associate, and additionally hints at a plausible biological role for the Grp94/OS-9 complex.